Early Postoperative Complications Following Modified Radical Mastectomy with Level II Axillary Dissection - Muhammad Hamayun Khan, Sohaib Mohammad Khan, Aftab Alam, Iram Bashir, Aftab Hussain, Ali Raza (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Modified Radical Mastectomy (MRM) with Level II axillary dissection is a common surgical procedure for breast cancer. However, early postoperative complications remain a concern for patient recovery. This study aimed to evaluate early postoperative complications, identify risk factors, and explore their association with patient demographics. Methods: A retrospective analysis was conducted on 105 patients who underwent MRM with Level II axillary dissection. Data was collected on demographics, postoperative complications, and risk factors, followed by logistic regression analysis. Results: The most common complications observed were seroma formation (34.3%), wound infection (17.1%), and lymphedema (13.3%). Significant risk factors for complications included obesity, age, diabetes, and smoking. Conclusion: This study highlights the common complications following MRM with Level II axillary dissection and identifies significant risk factors that can guide postoperative management strategies. Keywords: Modified radical mastectomy, axillary dissection, postoperative complications, breast cancer, seroma, lymphedema, risk factors.